Archaeology - Kelly, Robert L. (Boston, MA Cengage Learning, 2017)
Reflects the most recent research and changes in the field, while covering core concepts in an exceptionally student-friendly fashion by using personalized examples and high-interest topics -- Provided by the publisher.
Meet some real archaeologists -- The structure of archaeological inquiry -- Doing fieldwork : surveying for archaeological sites -- Doing fieldwork : why archaeologists dig square holes -- Geoarchaeology and site formation processes -- Chronology building : how to get a date -- The dimensions of archaeology : time, space, and form -- Taphonomy, experimental archaeology, and ethnoarchaeology -- People, plants, and animals in the past -- Bioarchaeological approaches to the past -- Reconstructing social and political systems of the past -- The archaeology of the mind -- Understanding key transitions in world prehistory -- Historical archaeology : insights on American history -- Caring for our cultural heritage -- Archaeology's future.
Includes bibliographical references (pages 366-383) and index.
Keywords: Archaeology -- Textbooks; Excavations (Archaeology)